2020
DOI: 10.9734/jamb/2020/v20i1030290
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activity of Aqueous and Ethanolic Leaf Extracts of Balanites aegyptiaca (l.) Del Plant on Some Selected Clinical Human Pathogens

Abstract: The antibacterial activity of the leaf extract of Balanites aegyptiaca plant was investigated on five selected clinical common human pathogens: Staphylococcus aureus, Streptococcus pneumonia, Salmonella typhimurium, Shigella dysentriae and Escherichia coli, in vitro. The phytochemical screening, susceptibility testing and Minimal Inhibitory Concentrations were determined. Preliminary phytochemical screening of the leaf extracts indicated the presence of alkaloids, cardiac glycosides, flavonoids, glycosides, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This residue cloudiness could therefore explain the higher mass yield in AE (24,3%) compared to EE (13,4%). Several authors [17,18,24,25] reported observations similar to our findings while others [26,27] found opposite results. Therefore, as…”
Section: -1-dry Matter and Extraction Yieldsupporting
confidence: 88%
“…This residue cloudiness could therefore explain the higher mass yield in AE (24,3%) compared to EE (13,4%). Several authors [17,18,24,25] reported observations similar to our findings while others [26,27] found opposite results. Therefore, as…”
Section: -1-dry Matter and Extraction Yieldsupporting
confidence: 88%
“…Callus cultivation presents a promising avenue for in vitro production of natural bioactive chemicals, providing an opportunity to harness and exploit plant-derived compounds for various therapeutic applications. [26] The alcoholic extract from the fruit of Balanites aegyptiaca demonstrated potent antifungal efficacy against a range of Candida species and opportunistic fungi. The Minimum Inhibitory Concentration (MIC) of the alcoholic extract varied from 3.05 to 24.0 g/ml for Candida species and 1.53 to 49.0 g/ml for opportunistic fungi.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Besides that also, Abdelaziz et al derivatives from its bark proved their potentials to cure yellow fever, as well as jaundice and syphilis (Hassan et al, 2016;Joel, 2018;Tesfaye, 2015). While some studies have reported and proved the uses of aqueous leaf and fruit extracts of B. aegyptiaca as an antifungal (Abdallah et al, 2012;Khatoon et al, 2013;Sawadogo et al, 2020;Singh et al, 2017), others illustrated their antibacterial and anti-inflammatory potentiality (Ezemokwe et al, 2020;Khamis et al, 2020;Murthy et al, 2021;Tula et al, 2014).…”
Section: Medicinal Usesmentioning
confidence: 99%